Compact high-performance dual-frequency power divider based on TSV. (November 2022) - Wang, Fengjuan; Li, Ruiqi; Yin, Xiangkun; Yu, Ningmei; Yang, Yuan
Abstract: In this paper, a dual-frequency compact power divider based on silicon via (TSV) is proposed. The matrix analysis method is used to convert the microstrip structure into Π-type structure, which improves the integration of the circuit. The proposed dual-frequency power divider structure is simulated and verified with High Frequency Structure Simulator (HFSS). The results show that the two frequency points of the dual frequency power divider structure are 10 GHz and 20 GHz respectively. In the low frequency band, the input return loss, and isolation are all lower than −15dB from 6.5 to 14.6 GHz. Insertion loss is better than −3.1 dB. In the high band, input return loss and isolation are all below −15dB from 15.3 to 20.8 GHz. Insertion loss is better than −3.3 dB. In addition, the size of the dual frequency power divider is only 0.2 × 0.428 mm 2 (0.009 × 0.004 λ g 2 ).